Factors affecting the incidence of chronic lung disease of prematurity in 1987, 1992, and 1997. Issue 1 (1st July 2001) - Manktelow, B N; Draper, E S; Annamalai, S; Field, D
Abstract : OBJECTIVE: To determine changes in the incidence of chronic lung disease of prematurity between 1987, 1992, and 1997. METHODS: Observational study based on data derived from a geographically defined population: Trent Health Region, United Kingdom. Three time periods were compared: 1 February 1987 to 31 January 1988 (referred to as 1987); 1 April 1992 to 31 March 1993 (referred to as 1992); 1997. All infants of ⩽ 32 completed weeks gestation born to Trent resident mothers within the study periods and admitted to a neonatal unit were included. Rates of chronic lung disease were determined using two definitions: ( a ) infants who remained dependent on active respiratory support or increased oxygen at 28 days of age; ( b ) infants who remained dependent on active respiratory support or increased oxygen at a corrected age of 36 weeks gestation. RESULTS: Between 1987 and 1992 there was a fall in the birth rate, but a significant increase was noted in the number of babies of ⩽ 32 weeks gestation admitted to a neonatal unit. There was no significant change in survival when the two groups of infants were directly compared. However, mean gestation and birth weight fell. Adjusting for this change showed a significant improvement in survival (28 day survival: odds ratio (OR) = 1.69; 95% confidence interval (95% CI) = 1.23 to 2.33. Survival to 36 week corrected gestation: OR = 1.45; 95% CI = 1.06 to 1.98). These changes were accompanied by a large increase in the incidence of chronic lung disease even after allowing for the change in population characteristics (28 day definition: OR = 2.20; 95% CI = 1.47 to 3.30. 36 week definition: OR = 3.04; 95% CI = 1.91 to 4.83). Between 1992 and 1997 a different pattern emerged. There was a further increase in the number of babies admitted for neonatal care at ⩽ 32 weeks gestation despite a continuing fall in overall birth rate. Survival, using both raw data and data corrected for changes in gestation and birth weight, improved significantly in 1997 (adjusted data: 28 day survival: OR = 1.72 (95% CI = 1.22 to 2.38); survival to 36 week corrected gestation: OR = 1.90 (95% CI = 1.36 to 2.64)). Rates of chronic lung disease showed no significant change between 1992 and 1997 despite improved survival (adjusted data: 28 day definition: OR = 0.72 (95% CI = 0.50 to 1.03); 36 week definition: OR = 0.88 (95% CI = 0.61 to 1.26). CONCLUSIONS: Current high rates of chronic lung disease are the result of policies to offer neonatal intensive care more widely to the most immature infants. Recent improvements in survival have been achieved without further increases in the risk of infants developing chronic lung disease.